Pengaruh Literasi Keuangan terhadap Pengelolaan Keuangan UMKM di Era Digital - Hasanah, Ulfah Yuziya; R, Rino (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Financial literacy plays a crucial role in ensuring the sustainability of micro, small, and medium enterprises (MSMEs), especially as they navigate the challenges of the digital economy. However, many MSMEs still face financial mismanagement due to limited knowledge and capabilities. This study aims to examine the influence of financial literacy on financial management practices among MSME actors in the digital era. The research used a quantitative approach with a descriptive-causal design, involving 250 MSME respondents from five major cities in Indonesia. Data were collected through structured questionnaires and analyzed using multiple linear regression. The findings reveal that financial literacy has a significant and positive effect on financial management, with a contribution of 37.7% to the variation in financial management practices. MSMEs with higher financial literacy were more likely to adopt digital financial tools and demonstrate better budgeting, record-keeping, and debt management. The study concludes that improving financial literacy is a strategic step to enhance the financial resilience and digital adaptability of MSMEs. These findings highlight the need for targeted education and support programs to strengthen the financial capacity of small business actors in the digital economy landscape.